Examining the Effects of Acute Cognitively Engaging Physical Activity on Cognition in Children - Bedard, Chloe; Bremer, Emily; Graham, Jeffrey D.; Chirico, Daniele; Cairney, John (Frontiers in Psychology, 2021)
Cognitively engaging physical activity (PA) has been suggested to have superior effects on cognition compared to PA with low cognitive demands; however, there have been few studies directly comparing these different types of activities. The aim of this study is to compare the cognitive effects of a combined physically and cognitively engaging bout of PA to a physical or cognitive activity alone in children. Children were randomized in pairs to one of three 20-min conditions: (1) a cognitive sedentary activity; (2) a non-cognitively engaging PA; and a (3) cognitively engaging PA. Executive function (EF) was assessed using a modified Eriksen flanker task immediately before and 10-15 min following the experimental condition. Children ages 6 to 8 years (n=48, Mage = 7.04, SD = 1.37; 40% girls) were included in the study. A repeated measures ANOVA found no significant difference between groups with respect to scores on the flanker task. The results do not support the hypotheses that a cognitively engaging bout of PA enhances cognitive performance over non-cognitively engaging PA or sedentary activities. Possible explanations for our findings include overexertion during the acute bout of PA and depletion of positive affect prior to performing the post-intervention EF tasks.